2005
DOI: 10.1093/eurpub/cki144
|View full text |Cite
|
Sign up to set email alerts
|

Travel and health status: a survey follow-up study

Abstract: In this study, travel had a positive effect on the perceived health status of the traveller. The positive effects of travel seemed to outweigh the impact of health problems. Travel did not lead to increased health-related costs, neither in individual health expenses nor indirectly through increased medical consultation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
7
17
1
1
Order By: Relevance
“…The most common single diagnosis was acute gastroenteritis (23%), consistent with previous findings on illness abroad [2,[8][9][10][11][12][13][14]28], accounting for one third of inpatient cases. Respiratory infections proved nearly as common (21%), yet with less frequent hospitalisation than for gastroenteritis.…”
Section: Results In Relation To Findings In Other Studiessupporting
confidence: 88%
See 4 more Smart Citations
“…The most common single diagnosis was acute gastroenteritis (23%), consistent with previous findings on illness abroad [2,[8][9][10][11][12][13][14]28], accounting for one third of inpatient cases. Respiratory infections proved nearly as common (21%), yet with less frequent hospitalisation than for gastroenteritis.…”
Section: Results In Relation To Findings In Other Studiessupporting
confidence: 88%
“…Respiratory infections proved nearly as common (21%), yet with less frequent hospitalisation than for gastroenteritis. In prospective studies, respiratory infections have been reported in 2-26% of travellers [2,[7][8][9][10][11][12][13][14].…”
Section: Results In Relation To Findings In Other Studiesmentioning
confidence: 99%
See 3 more Smart Citations